2009
DOI: 10.1007/s11671-009-9469-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Lecithin Nanoemulsion as a Topical Delivery System

Abstract: Purpose of this study was to establish a lecithin nanoemulsion (LNE) without any synthetic surfactant as a topical delivery vehicle and to evaluate its topical delivery potential by the following factors: particle size, morphology, viscosity, stability, skin hydration and skin penetration. Experimental results demonstrated that an increasing concentration of soybean lecithin and glycerol resulted in a smaller size LNE droplet and increasing viscosity, respectively. The droplet size of optimized LNE, with the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(67 citation statements)
references
References 34 publications
4
60
0
3
Order By: Relevance
“…Full factorial experimental design During the nanoemulsion development, a two-level 2 3 full factorial experimental design was used to identify and estimate the main and interaction effects of three different formulation factors (oil type -A, oil content -B, and presence of model drug -C) on critical quality attributes of the developed nanoemulsions. Each factor was varied at two coded (-1, +1) levels, in which the -1 level corresponds to the lower value and +1 to the upper value of each independent variable (Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full factorial experimental design During the nanoemulsion development, a two-level 2 3 full factorial experimental design was used to identify and estimate the main and interaction effects of three different formulation factors (oil type -A, oil content -B, and presence of model drug -C) on critical quality attributes of the developed nanoemulsions. Each factor was varied at two coded (-1, +1) levels, in which the -1 level corresponds to the lower value and +1 to the upper value of each independent variable (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the formulation and physicochemical characteristics, nanoemulsions have been associated with a number of advantages such as a low surfactant concentration, a uniform and very small droplet size, low viscosity, and high solubilization capacity for lipophilic drugs. Additionally, the improved penetration through biological barriers, possible enhanced bioavailability and organ targeting could be expected with these systems [1][2][3][4][5][6]. Although lipid nanoemulsions have been traditionally employed for parenteral nutrition and intravenous delivery of lipophilic drugs -with several approved products on the market -the additional efforts are required to optimize nanoemulsion formulation, stability, and overall drug delivery [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…Xerosis is said to be one of the very significant parameter in AD pathophysiology, which has both cause and effect dimensions to it. Formulations which increase skin hydration are expected to useful in management of AD 10,25 . Ex-vivo studies across rodent skin in a Franz diffusion cell demonstrated that less than 10% drug permeates transdermally into the receptor compartment from optimized formulation as well as marketed cream preparation.…”
Section: Fig 2: Response Surface Plot For Q8mentioning
confidence: 99%
“…This leads to increased skin hydration, which may promote the absorption of topically applied drugs or cosmetics. 12 The very small droplet size greatly reduces the gravitational force, 13 and Brownian motion largely prevents gravitationally driven sedimentation or creaming. 6,10,14 The transparent nature of O/W nanoemulsions, their good fluidity, and the absence of any thickeners give them a pleasant aesthetic character and skin feel.…”
Section: Introductionmentioning
confidence: 99%